Organic Matter Sources and Black Carbon Fractions Shape Mercury Partitioning in Intertidal Sediments of the Yangtze Estuary - Xinyu Hu; Lumin Sun; Bing Xie; Haojun Guan; Jiahong Zeng; Zikun Song; Changyi Lu (Journal of Marine Science and Engineering, 2026)
Estuarine intertidal sediments are important sinks for riverine mercury (Hg), yet the effects of organic matter sources and BC fractions on Hg partitioning are still poorly understood. We analyzed sediments from reed-covered and unvegetated flats in the Yangtze Estuary for total Hg (THg), operationally defined Hg fractions, total organic carbon (TOC), total nitrogen (TN), n-alkanes, and BC fractions (char and soot). THg ranged from 60.3 to 228.5 ng g−1, averaging 114.6 ± 38.9 ng g−1. THg was significantly higher in reed-covered sediments and in surface layers, and was positively correlated with TOC and TN (p < 0.01, n = 20), indicating that vegetation-driven organic matter accumulation promoted Hg enrichment. Hg partitioning differed between habitats: reed-covered sediments showed co-dominance of oxidizable Hg and residual Hg, whereas unvegetated flats were dominated by residual Hg (62.0 ± 10.8%), suggesting stronger Hg stabilization in the absence of fresh plant inputs. n-Alkane patterns indicated that vegetation type controlled sediment organic matter composition more strongly than site or depth. While no significant correlations were observed between BC fractions and Hg fractions in individual habitats, soot exhibited significant positive correlations with labile Hg (acid-soluble and reducible Hg) in a depth-averaged analysis of merged surface and subsurface layers (p < 0.05, n = 10), a preliminary signal constrained by the small number of sites, which suggests that soot may facilitate the sedimentary retention of reactive Hg. These results highlight source-specific controls on Hg partitioning beyond bulk TOC.

Mercury migration during leaf litter decomposition in a coastal artificial mangrove wetland - Rui Wu; Lumin Sun; Yuting Xiao; Jue Zheng; Ziyan Huang; Xinyi Yang; Dongxing Yuan; Changyi Lu (Marine Pollution Bulletin, 2026)

Reactive molecular dynamics study on the evolution of components and nitrogen migration pathways in plasma assisted ammonia combustion - Lumin Chen; Mingyan Gu; Kun Luo; Jingyun Sun; Longwei Chen; Yang Wang (Fuel, 2025)

Mercury distribution and transfer in mangrove forests in urban areas under simulated rising sea levels - Xilin You; Lumin Sun; Xiaozheng Chen; Yiting Li; Jue Zheng; Dongxing Yuan; Junjie Wu; Shiyu Sun (Frontiers in Marine Science, 2024)
This study assesses the impact of simulated sea level rise (SLR) on mercury distribution and migration in an urban mangrove wetland on the northern coast of Maluan Bay, Xiamen City, Fujian Province, China. Two adjacent Kandelia obovata mangrove plots with elevations representing current sea level and a 40-cm SLR were examined. Total mercury (THg), methylmercury (MeHg), and mercury isotopes in sediments from different elevations were analyzed to reveal the geochemical behavior of mercury under a simulated 100-year SLR scenario. THg and MeHg distribution in sediments mirrored patterns of biogenic elements (carbon, nitrogen, and phosphorus), suggesting adsorption onto organic matter as the primary entry mechanism. Low-elevation plots showed significantly higher concentrations of THg, MeHg, total organic carbon (TOC), total nitrogen (TN), and total phosphorus (TP) compared to high-elevation plots. Mercury isotope characteristics indicated that the primary mercury source was anthropogenic emissions from surrounding lands, entering the wetland from both landward and seaward directions. The study highlights the crucial role of mangrove wetlands in mercury pollution control and nutrient cycling under SLR conditions. Results suggest that SLR enhances the retention capacity of mangrove wetlands for THg, MeHg, and nutrients. This research provides a scientific basis for mangrove conservation and restoration, offering new insights into the geochemical behavior of mercury in vegetated intertidal ecosystems in the context of climate change.

A novel 1D MXene fibers-loaded metal-organic framework derived bimetallic sulfide for high-performance supercapacitors - Jianhao Lao; Yanling Zhu; Fen Xu; Lixian Sun; Songwen Fang; Qiwei Shao; Lumin Liao; Yanxun Guan; Yongjin Zou (Fuel, 2024)

Mercury Sources and Processes Implied by Other Pollutants Distributions in Surface Water and Sediments of a Subtropical Estuary in Southern China - Xiaodan Zhang; Lumin Sun; Xianxu Huang; Jingting Zhuang; Zhenbin Gong; Dongxing Yuan (Water, Air, & Soil Pollution, 2022)

Distribution and Transformation of Mercury in Subtropical Wild-Caught Seafood from the Southern Taiwan Strait - Lumin Sun; Weijia Chen; Dongxing Yuan; Liang Zhou; Changyi Lu; Yingjie Zheng (Biological Trace Element Research, 2022)

Variations in the isotopic composition of stable mercury isotopes in typical mangrove plants of the Jiulong estuary, SE China - Lumin Sun; Bingyan Lu; Dongxing Yuan; Wenbo Hao; Ying Zheng (Environmental Science and Pollution Research, 2017)

Effect on the Photo-production of Dissolved Gaseous Mercury in Post-desulfurized Seawater Discharged from a Coal-Fired Power Plant - Lumin Sun; Bingyan Lu; Dongxing Yuan; Cheng Xue (Water, Air, & Soil Pollution, 2015)

The distribution and sea–air transfer of volatile mercury in waste post-desulfurization seawater discharged from a coal-fired power plant - Lumin Sun; Shanshan Lin; Lifeng Feng; Shuyuan Huang; Dongxing Yuan (Environmental Science and Pollution Research, 2013)

Mercury distribution in seawater discharged from a coal-fired power plant equipped with a seawater flue gas desulfurization system - Xiyao Liu; Lumin Sun; Dongxing Yuan; Liqian Yin; Jinsheng Chen; Yaoxing Liu; Chengyu Liu; Ying Liang; Fangfang Lin (Environmental Science and Pollution Research, 2011)